2020
DOI: 10.4103/psychiatry.indianjpsychiatry_357_19
|View full text |Cite
|
Sign up to set email alerts
|

Nonadherence in bipolar disorder patients: A 14-year retrospective study

Abstract: Background: Bipolar disorder is a disabling psychiatric disorder. The existing literature suggests about 41% of patients to be nonadherent. Nonadherence leads to relapses, delay in recovery besides higher inpatient care cost as well as higher global cost of the disease. Nonadherence in bipolar affective disorder (BPAD) is a complex phenomenon, its critical determinants are yet to be identified with certainty. Aims: This study aims to assess the prevalence of nonadherenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…[ 24 , 35 ] Several studies did not find any association between gender and MNA. [ 10 , 15 , 17 , 20 , 21 , 24 , 36 - 38 , 40 , 41 , 46 , 47 ] Four studies found that compliance was better in females,[ 25 , 26 , 33 , 35 ] while one study found that female gender was associated with MNA. [ 7 ] Most studies did not find any association between education and MNA.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[ 24 , 35 ] Several studies did not find any association between gender and MNA. [ 10 , 15 , 17 , 20 , 21 , 24 , 36 - 38 , 40 , 41 , 46 , 47 ] Four studies found that compliance was better in females,[ 25 , 26 , 33 , 35 ] while one study found that female gender was associated with MNA. [ 7 ] Most studies did not find any association between education and MNA.…”
Section: Resultsmentioning
confidence: 99%
“…[ 7 ] Most studies did not find any association between education and MNA. [ 7 , 10 , 15 , 17 , 21 , 24 , 33 , 35 , 37 , 39 , 40 , 46 ] Lower education was associated with noncompliance in some studies[ 20 , 26 ] and greater literacy was associated with better compliance in one study. [ 41 ] Marital status did not associate with MNA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study identified a gap in the research conducted on this phenomenon. Some other literature concentrated on poor adherence to medication in patients with bipolar mood disorders and severe depression who were non-adherent to their prescribed medications [16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%